Interferon-Based Therapy for Chronic Hepatitis C: Present and Future Perspectives (TAJ: Journal of Teachers Association, 2009)
Pegylated interferon α (peginterferon α) plus ribavirin is the present mainstay of treatment for patients with chronic HCV infection. When peginterferon α plus ribavirin is administered for the standard duration, a sustained virological response is achieved in around 50% of patients infected with HCV genotype 1 and around 80% of patients infected with HCV genotype 2 or 3. Data now suggest that treatment duration can be shortened or lengthened depending on baseline viral load and/or early on-treatment viral kinetics, offering the prospect of individualizing therapy further to improve response or to prevent treatment from being unnecessarily extended. Further efforts to optimize therapy are likely to involve the use of new anti-HCV agents, several of which are currently in the early stages of development. These agents include HCV protease inhibitors (particularly those against NS3-4A protease), HCV polymerase inhibitors (including both nucleoside and non-nucleoside analogs) and cyclophilin inhibitors. These compounds will be used, at least initially, in combination with peginterferon α plus ribavirin, extending the pivotal role of interferon-based therapy in the management of chronic hepatitis C. doi: 10.3329/taj.v21i2.3804 TAJ 2008; 21(2): 182-193